Evaluating Digital Readiness and Teachers’ Perceptions of a Digital Based Performance Appraisal System in Secondary Schools - Karuniawan, Heru; Mutawalli, Lalu; Imtihan, Khairul (Universitas Bina Darma, 2025)
This study investigates the determinants influencing the adoption of digital based performance appraisal systems in secondary schools by integrating the Technology Acceptance Model (TAM) with the Technology Organization Environment (TOE) framework. A quantitative approach was employed, involving 103 teachers from junior and senior secondary schools, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and Importance Performance Map Analysis (IPMA). The results show that perceived ease of use strongly affects both perceived usefulness (β = 0.377, p = 0.007) and behavioral intention (β = 0.678, p < 0.001). Environmental readiness (β = 0.495, p < 0.001) and technological readiness (β = 0.357, p < 0.001) are significant predictors of perceived ease of use, while organizational readiness (β = 0.269, p = 0.013) significantly influences perceived usefulness. Conversely, the direct effect of perceived usefulness on behavioral intention was not significant (p = 0.142). The IPMA results emphasize that although environmental and technological readiness exhibit relatively high performance, they still present opportunities for improvement to enhance perceived ease of use. These findings highlight that strengthening usability, infrastructure, and organizational support is crucial for increasing teacher acceptance and ensuring the sustainable implementation of digital based performance appraisal systems in schools.